Impact of neighborhood biomass cooking patterns on episodic high indoor particulate matter concentrations in clean fuel homes in Dhaka, Bangladesh. (23rd September 2013) - Salje, H.; Gurley, E. S.; Homaira, N.; Ram, P. K.; Haque, R.; Petri, W.; Moss, W. J.; Luby, S. P.; Breysse, P.; Azziz‐Baumgartner, E.
Abstract Exposure to particulate matter (PM2.5) from the burning of biomass is associated with increased risk of respiratory disease. In Dhaka, Bangladesh, households that do not burn biomass often still experience high concentrations of PM2.5, but the sources remain unexplained. We characterized the diurnal variation in the concentrations of PM2.5 in 257 households and compared the risk of experiencing high PM2.5 concentrations in biomass and non‐biomass users. Indoor PM2.5 concentrations were estimated every minute over 24 h once a month from April 2009 through April 2010. We found that households that used gas or electricity experienced PM2.5 concentrations exceeding 1000 μg/m3 for a mean of 35 min within a 24‐h period compared with 66 min in biomass‐burning households. In both households that used biomass and those that had no obvious source of particulate matter, the probability of PM2.5 exceeding 1000 μg/m3 were highest during distinct morning, afternoon, and evening periods. In such densely populated settings, indoor pollution in clean fuel households may be determined by biomass used by neighbors, with the highest risk of exposure occurring during cooking periods. Community interventions to reduce biomass use may reduce exposure to high concentrations of PM2.5 in both biomass and non‐biomass using households.